Phylogenetic relationships of Ibervillea and Tumamoca (Coniandreae, Cucurbitaceae), two genera of the dry lands of North America - Lira, Rafael; Sosa, Victoria; Legaspi, Talitha; Dávila, Patricia (Phytotaxa, 2015)
We examine the limits and phylogenetic relationships of Ibervillea and Tumamoca belonging to tribe Coniandreae in the Cucurbitaceae. These taxa are found in xeric areas from southern United States to Guatemala. There has been no previous phylogenetic studies considering all their taxa together, just partially. Furthermore, we include as well species of Dieterlea, another similar and sympatric genus which recognition is under debate, formerly considered as a synonym of Ibervillea. Using molecular and morphological characters we performed molecular and total evidence parsimony and Bayesian analyses. Our results confirm that species in Ibervillea and Dieterlea are part of a monophyletic group, supporting the integration of both genera as proposed in previous phylogenetic and taxonomic studies. By examining all the species of the three genera, our results are the first to suggest that Tumamoca is also part of this monophyletic group. Therefore we propose that the species of Ibervillea, Dieterlea, and one species of Tumamoca should be included into the same genus. According to the priority rule, Ibervillea is the name to be used. Tumamoca macdougalli needs to be transferred to Ibervillea and the combination is made here. We suggest that the second species in Tumamoca, T. mucronata, known by a single specimen that is lost, does not deserve recognition.